COMMUNITY PARTICIPATION IN PLANNING VILLAGE DEVELOPMENT IN SOUTH BOLAANG MONGONDOW - Rizal; Hairudin Anwar; Azis Rachman (Journal of Economic, Business, and Administration (JEBA), 2024)
This study aims to: (1) determine and analyze community participation in village development planning in Bolaang Mongondow Selatan. (2) Knowing and analyzing the factors that determine community participation in village development planning in South Bolaang Mongondow. This research is a research with a qualitative descriptive approach, namely examining, analyzing and decrypting the data. Research result : (1) Community participation in South Bolaang Mongondow Regency in village development planning is quite good, it can be seen from the attendance list of activity participants. Not all of the community's proposals were accommodated, due to budget constraints. Community activity in implementing the community's willingness to help in the form of materials, energy and thoughts. Community activity in evaluation / monitoring can be seen from each activity being directly supervised by community groups. The activity in this utilization can be seen from the recipients of the RTLH and family latrines, the use of kindergarten school classrooms. (2) The determinants of community participation in Bolaang Mongondow Selatan which in this study consisted of 7 elements: age, education level, type of work, income level of the population, length of stay, communication and leadership. Based on the analysis of researchers from the results of interviews, the most dominant factor is leadership on the grounds that leadership is a very important factor in influencing community participation, good leadership is one that divides authority and responsibility in the community, without reducing participation and responsibility to other communities. The leader must be able to influence the community so that they are willing to participate in achieving the goals that have been set.